KONSTRUKSI DISIPLIN ANAK MELALUI METODE PEMBIASAAN PADA TK AL ASY’ARI KABUPATEN BONDOWOSO TAHUN 2023-2024 - Emy Indah Shofiyati; Khoiriyah, Khoiriyah; Misyana, Misyana (Bajang Institute, 2024)
The aim of the research is to describe the habituation methods used by teachers in children's discipline at school through the habituation method. This research was conducted at the Al Asy'ari Kindergarten institution, Sumber Kalong village, Wonosari District, Bondowoso Regency. The type of research used was descriptive qualitative which aims to describe the habituation methods used by teachers in children's discipline at school through the habituation method. In this research, researchers used a qualitative description method. Qualitative descriptive research, where descriptive research is a statement of research questions, directly explores or photographs the social context to be studied in depth and breadth. Qualitative methods are research procedures that produce descriptive data in the form of people's written or spoken words and observed behavior. The object of research is the class B teacher. Children's discipline is visible from the moment they come to school in the morning material and core activities until they go home. This is in accordance with the results of an interview with the Head of Al Asy'ari Kindergarten which stated that: The development of children's discipline is achieved through a combination of structured and spontaneous activities. In the school environment, in forming disciplinary attitudes in children at school, the habituation method is a very effective approach. Teachers have an important role in implementing this method. By modeling good behavior, providing positive reinforcement, and establishing consistent routines, teachers can help children understand, internalize, and apply the values ​​of discipline in their daily lives.